2016
DOI: 10.1007/s00442-016-3646-x
|View full text |Cite
|
Sign up to set email alerts
|

Spectral determination of concentrations of functionally diverse pigments in increasingly complex arctic tundra canopies

Abstract: As the Arctic warms, tundra vegetation is becoming taller and more structurally complex, as tall deciduous shrubs become increasingly dominant. Emerging studies reveal that shrubs exhibit photosynthetic resource partitioning, akin to forests, that may need accounting for in the "big leaf" net ecosystem exchange models. We conducted a lab experiment on sun and shade leaves from S. pulchra shrubs to determine the influence of both constitutive (slowly changing bulk carotenoid and chlorophyll pools) and facultati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Other carotenoids were sometimes involved, especially antheraxanthin and zeaxanthin. Total carotenoid estimation has been widely assessed using VI, but only few studies attempted to separate carotenes and xanthophylls (Boelman et al 2016, Stylinski et al 2002. Our study showed that it is of great importance for understanding the biochemical and spectral responses of vegetation to TPH and HM exposure.…”
Section: Relationship Between Biochemical and Spectral Responsesmentioning
confidence: 85%
“…Other carotenoids were sometimes involved, especially antheraxanthin and zeaxanthin. Total carotenoid estimation has been widely assessed using VI, but only few studies attempted to separate carotenes and xanthophylls (Boelman et al 2016, Stylinski et al 2002. Our study showed that it is of great importance for understanding the biochemical and spectral responses of vegetation to TPH and HM exposure.…”
Section: Relationship Between Biochemical and Spectral Responsesmentioning
confidence: 85%
“…Photosynthetic pigment composition and dynamics in arctic and sub-arctic plants has rarely been studied. To the best of our knowledge only one recent publication describes in detail carotenoid composition in leaves of Salix pulchra in northern Alaska tundra (68°63'N) (Boelman et al 2016) and, at a much higher latitude (Spitsbergen 78°04'N) bulk carotenoids and chlorophylls have been studied in a couple of bryophytes, lichens and vascular plants, but by non-resolutive spectrophotometric techniques (Shmakova 2010). In the three species analysed in our work, pigment composition (Fig.…”
Section: Discussionmentioning
confidence: 99%